Activisme radical et attention continuelle: Une tentative de défense de Pierre de Jean Olivi - Solère, Jean-Luc (Recherches de théologie et philosophie médiévales, 2024)
Arguing for a cognition theory that radically rejects the passivity Aristotle attributes to the soul with regard to material things, Olivi has to assume that the soul is always on the alert, that is, that its attention to the body never disappears, even in deep sleep. This is for him the only way to explain why an intense sensation wakes us up without acting on the soul. He thus exposes himself to possible criticism from Aristotelians: his hypothesis is counter-intuitive and seems to be contradicted by our experiencing eclipses of our awareness. I propose a defense of Olivi based on a ‘retort’, showing that Aristotelians must themselves postulate either, like Albert the Great, that the agent intellect is constantly in act, or, like Thomas Aquinas, that it exercises a continual surveillance of phantasms, even when we are not conscious of it. So they cannot deny Olivi the right to hypothesize a permanent attention of the soul.